P15 How important are blood cultures in the management of patients suspected to have Community Acquired Pneumonia?. (19th November 2012) - Kent, W; Potter, L; Roberts, S; Shaw, R; Vaudrey, K; Deegan, P; Folb, J
Abstract : Background: It is acknowledged in the BTS guidelines that the routine use of blood cultures in community acquired pneumonia (CAP) has been questioned on the grounds of cost, low sensitivity and lack of impact on antimicrobial management. 1 In October 2011 the hospital policy for severe CAP (CURB 65 ≥ 3) at our trust changed to benzylpenicillin and clarithromycin. This combination is associated with decreased rates of clostridium difficile, however it has weak cover against Haemophilus influenzae and none against gramme negative bacilli. Aim: To determine the positive yield from blood cultures in patients suspected as having CAP at presentation to hospital, their impact on management and, in particular, the outcomes associated with Gram negative bacteraemia. Method: Patients were prospectively identified at a large University Hospital in whom CAP was suspected as their admitting diagnosis between November 2011 and January 2012. The patient demographics and outcomes were analysed at admission and revisited at 7 and 30 days. Results: 151 patients were identified for inclusion. Age range was 22–97, median 75. The CXR was reported as showing infiltrates in 93/148 cases (62.8%). Blood cultures were sent in 41/88 patients (46.5%) with CURB score ≥ 2 and 21/37 patients (56.8%) with CURB score ≥ 3. There were 10 positive blood cultures (representing 14.5% of all blood cultures sent). 6 were positive for streptococcus pneumoniae and 4 yielding E. Coli or Klebsiella suggesting an alternative source of infection. There were no cases of severe CAP due to Haemophilus influenzae. 60/151 patients had a change in their antibiotics; 11 as a result of poor clinical progress, 11 due to positive microbiology results, 38 due to a new diagnosis or no evidence of infection. Conclusion: Blood cultures can be of increased importance in the investigation of CAP when used in combination with a narrower spectrum of antibiotics, particularly when checking for the possibility of occult gram negative sepsis. References: Lim WS et al. Pneumonia Guidelines Committee of the BTS Standards of Care Committee. BTS guidelines for the management of community acquired pneumonia in adults: update 2009. Thorax. 2009.Oct; 64 Suppl 3:iii 1–55.